High-Reliability Thermoreceptors with Minimal Temporal and Spatial Variations Through Photo-Induced Patterning Thermoelectrics - Chunyu Du; Yue Hu; Xiao Xiao; Farid Manshaii; Lirong Liang; Jun Chen; Guangming Chen (Nano-Micro Letters)
Highlights A novel photobase generator is specifically designed for the fabrication of high-resolution sensing devices. Similarities in pain perception mechanism between thermoelectric-based artificial thermoreceptor and biological nociceptor. Emulation common nociceptive behaviors and pain response under excessive temperature stimuli.